Agrotourism potential as part of sustainable rural development in Romania - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The rural economy is more developed and more dynamic if it has a more diverse structure, and if the share of non-agricultural economy is higher. In this context, the agrotourism is a field that is growing in popularity as producers try to diversify their activities and increase profits that can support economic development in the countryside through sustainable use of tourism resources and maintaining the rural community cultural and social diversity. Our paper focuses on specific opportunities and constraints that influence the progress of agrotourism activities as viable entrepreneurial solutions for self-sustainable rural communities in Romania from the perspective of European integration. The results have shown that agrotourism activity in the areas where it was implemented and developed, had a very strong and favourable impact not only on the economic and touristic framework of localities, but also on their social, cultural, spiritual and even ecological framework.
Keywords: Q01; R33; 330; sustainable development; non-agricultural activities; agro-tourism; Romania